Self Care Berhubungan dengan Kadar Gula Darah Pasien Diabetes Melitus Tipe 2 - Zakiah Rahman; Wasis Pujiati; Hotmaria Julia Dolok Saribu (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the relationship between self-care and blood sugar levels in type 2 diabetes patients. This research method uses quantitative research with the analytic observational process with a cross-sectional approach. The study results showed a relationship between self-care and blood sugar levels in type 2 diabetes mellitus patients at Rumkital Dr. Midiyato Suratani, Tanjungpinang City, with the Chi-Square analysis test obtained a p-value of 0.002 (â‰¤0.05). In conclusion, there is a relationship between self-care and blood sugar levels in type 2 diabetes mellitus patients at Rumkital Dr. Midiyato Suratani Tanjungpinang. Keywords: Diabetes Mellitus Type 2, Blood Sugar Levels, Self-Care